Assessing the Needs of People with Disabilities in the Emirate of Abu Dhabi, UAE - Gaad, Eman (Journal of Education and Vocational Research, 2013)
While there are many opportunities for people with disabilities (PWD) in Abu Dhabi (AD), UAE, there hardly been a study of what is required to get such people to meet their full potentials. This study commenced December 2012 and lasted for 4 months. The needs assessment based study tried to answer questions like what is needed to achieve the enhancement of the quality of life of PWD in AD region during and after school/centre times. It also looked at what type of needs (financial, assistive, emotional, and other) those people might have, and what are the needs of the parents of PWD that support the development of their children to reach their full potentials. Adding to that what could be recommended to bridge the gap in such needs. The purpose was mainly to develop a good understanding of the landscape. Benchmarking was undertaken from all private centers and scanning the needs of all parents of PWD in government centers across AD as well. It is hoped that researching the findings would help to develop the services on offer for PWD in the Emirate of AD. In order to achieve the aims of this study, 8 centres were selected out of the total of 17 which is the number of private centres in AD. The selection was based on size, location and type of disability as a purposeful sample to insure fair representation of the centres. The researcher conducted 8 filed visits of centers in Abu Dhabi and Al Ain to assess their current services, operating model etc. Individual briefs were prepared for every center with comparisons across specific factors. Scanning all the needs of all the parents of people with disability in the government centres across Abu Dhabi was looked at differently. To insure validity of the data and because the Emirati people with disability clustered mainly in government centres, all nine government centres under Zayed Higher Organization for Humanitarian Care were visited and sample interviews (qualitative and quantitative) from all centres were undertaken. Selected participants were used to interview and investigate up close (purposeful sampling). Findings showed that there is a desperate need for support after school hours despite the care offered during school hours for those who are in school age. Parents need support on several levels especially with how to spend quality time with their children with disabilities.